Utility of assessment center for promotion of police sergeants. - Thornton GC III; Potemra MJ (Public Personnel Management)
Is the cost of an assessment center worth it? This study demonstrates the economic utility of an assessment center as a part of a promotional examination to police sergeant. The total cost of the program to assess 208 candidates was $158,970, or $764 per candidate. Based on initial promotions of 22 sergeants, total utility was estimated to be at least $414,943, utility per candidate was estimated to be at least $1995, and utility per selectee was estimated to be at least 518,861. Substantially higher estimates of utility were shown when alternative values of costs, validities of the assessment center, number of sergeants promoted over the life of the promotional list, and the benefits of selecting effective sergeants.